Crecimiento y longevidad en el pino canario (Pinus canariensis Smith.) - Genova, M.=700 1 Santana, C.
(En, Es)
Ilus., 19 ref.
Keywords: PINUS CANARIENSIS; ANILLO DE CRECIMIENTO; LONGEVIDAD; EDAD; ARBOLES; ESPAÑA